Juridical Analysis of Strict Liability Application in Forest and Land Fire Cases in Central Kalimantan Based on Law Number 32 of 2009 - Yacob F. Martono; Rollys Suriani (UNISSULA, 2025)
Forest and land fires (karhutla) in Central Kalimantan constitute a recurring environmental problem with massive economic, social, and ecological impacts. This research analyzes the application of the strict liability concept in forest and land fire cases in Central Kalimantan based on Law Number 32 of 2009 concerning Environmental Protection and Management. The research employs a normative juridical method with statutory and case approaches. Secondary data was obtained from primary legal materials in the form of legislation, secondary legal materials comprising literature and court decisions, and tertiary legal materials. The research results show that the concept of strict liability as regulated in Article 88 of Law Number 32 of 2009 establishes absolute liability without the requirement to prove fault for activities that pose a serious threat to the environment. Its application has proven effective in the PT Kumai Sentosa case with a compensation ruling of Rp 175.18 billion for environmental restoration covering 3,000 hectares. However, implementation still faces obstacles in proving causal relationships between business activities and forest fires, complexity in calculating ecological damages, inconsistency in court decisions, and weak execution mechanisms. The study urges improved implementation via technology-based evidence, standardized damage calculations, and stronger judicial understanding.